POLA ASUH KELUARGA BURUH DALAM MENDIDIK KARAKTER ANAK (Studi Kasus Di Dukuh Banyurip Kelurahan Ngandong Kecamatan Gantiwarno Kabupaten Klaten) - Fitri Wulandari; Siti Mariah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The purpose of this research is to know: 1) Understanding labor family against character education children in terms of discipline, the responsibility, and rectitude . 2) Described a pattern family foster workers in developing character education children in terms of discipline, the responsibility, and rectitude. Research approach used in this research is a qualitative approach.The method of collecting data on the observation are interviews, and documentation.Data analysis technique research was done with alir models is data collection, the reduction of data, presentation of data, verification and affirmation of conclusion .The results of research found that 1) the subject of study about educating the character of a child in this discipline , responsibility , and honesty is good that is the discipline is regulation , good governance that must be obeyed child at home , the school , and the environment .The responsibility is running all obligations ( particularly in worship ) and readiness to bear the risks in all his works.Honesty is actually the words and behavior in accordance or balanced with the words .2 ) foster pattern applied the subject of research in educating the character of a child in terms of discipline responsibilities and honesty are good that is a pattern foster discipline by means of exercising, accustom; and teach values religious.Foster pattern responsibility by means of accompanying and to familiarize child to learn timely not procrastinate a job, keep their neighborhood clean and educating children to can handle himself, so that a child to be more independent. Foster pattern honesty by means of train the being honest must always control the use of the allowance is given.Â